Mengelola Hubungan Berbagai Stekeholders Dalam Manajemen Strategis - Rizadiliyawati; Dahrani; AminudinBusro; Muhammad Syaifudin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
The purpose of this study is to Manage Multi-Stakeholder Relationships in Strategic Management. The type of research used is literature study, data collection with documentation, data analysis with content analysis. In management strategy, management relationships with various stakeholders are crucial aspects that include the formation of strong networks and unity, understanding the dual roles carried out by various parties, and determining special roles in management. Networks and functions to create synergy and strategic alliances in achieving organizational goals, while dual roles require managerial abilities to handle conflicting interests wisely. On the other hand, special management roles are needed to facilitate communication, maintain trust, and create added value for all stakeholders. By managing these three aspects effectively, organizations can increase legitimacy, strengthen strategic positions, and ensure continuity in a dynamic and competitive environment.